Household formation and tenure choice: Did the great Irish housing bust alter consumer behaviour? - David Byrne; David Duffy; John FitzGerald (The Economic and Social Research Institute (ESRI), 2014)
This paper analyses the household formation and tenure choice decisions of different age cohorts in the Irish market. We use data covering the years 2001 to 2011, a period which encompasses the boom, bubble and collapse in the Irish housing market. We find that the household formation decision is affected by the rent-to-income ratio while tenure choice depends upon the difference between rent and the user cost of housing, a notional cost of services derived from owning a home. After the crash, the balance of these costs favoured renting, resulting in a decrease in owner occupancy. In addition, we find that falling average rents caused entry to the housing market to become more affordable, and that this is linked to significantly higher household fo rmation rates.
Keywords: 330